1994
DOI: 10.1046/j.1365-313x.1994.5060895.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular markers of embryogenesis in Arabidopsis thaliana by promoter trapping

Abstract: SummaryThe technique of promoter trapping has been exploited to identify markers of embryogenesis in Arabidopsis thallana. A population of transgenic A. thallana was generated containing the promoter trap vector pAgusBin19, following Agrobacferium tumefaciens-medlated transformation. This vector contains, at the T-DNA left border, a promoterless gusA gene, which is activeted following integration downstream of a native gene promoter that directs transgene transcription. Screening of a population of 430 indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 21 publications
0
54
1
1
Order By: Relevance
“…Previous studies showed that promoter trap GUS activity in the promoter trap line AtEM201 is constitutive throughout the four cell-stage, globular and heart-stage embryo ( Figure 1a; Topping et al, 1994). GUS activity in the mature embryo is strongest in the developing radicle, with weaker staining in the cotyledons.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Previous studies showed that promoter trap GUS activity in the promoter trap line AtEM201 is constitutive throughout the four cell-stage, globular and heart-stage embryo ( Figure 1a; Topping et al, 1994). GUS activity in the mature embryo is strongest in the developing radicle, with weaker staining in the cotyledons.…”
Section: Introductionmentioning
confidence: 82%
“…Previous T-DNA segregation and Southern analysis demonstrated that the promoter trap line AtEM201 contains a single copy T-DNA (Topping et al, 1994). Inverse PCR (IPCR) was used to generate 464 bp of T-DNA flanking sequence, presumed to contain part of the tagged EXO gene.…”
Section: Exordium Gene Cloningmentioning
confidence: 99%
See 3 more Smart Citations